Location-Based Service and Knowledge Management System Integration Prototyping of Historic Mosques Applications - Puput Irfansyah; Atie Ernawati; Ambar Tri Hapsari; Yogi Bachtiar; Diah Mariana; Achmad Zulkarami (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This paper discusses the prototype of integrating a knowledge management system with location-based services for an application that employs historical mosques. One problem that often comes up in local culture is keeping its identity. We must work together to keep it alive so the next generation can experience it. For example, the historic mosque is an essential part of Indonesian cultural heritage that needs to be protected because it has crucial spiritual, historical, social, and artistic values. Many cultural heritage items are in danger because of how quickly things change. As a result, it is essential to protect old mosques as part of Indonesia's cultural heritage. It can quickly look through ancient mosques and use them to guide religious-based heritage tourism by combining a knowledge management system (KMS) with a location-based service (LBS). Through KMS, information from different sources can be organized and clearly shown. This can help historic mosques and those nearby people be seen for what they can do. The study's goal is to create a prototype of the LBS-integrated KMS-based historic mosque application. Later, these features can help tourists find their way and learn about the nearby culture and people, such as the historical mosques in Lombok and Java. The results suggest that the system be implemented to make learning about and getting around historic mosques easier.